High temperature solid-catalyzed in-situ transesterification for biodiesel production - Talha, Nur Syakirah; Sulaiman, Sarina; Azmi, Azlin Suhaida (Penerbit UTM Press, 2017)
In-situ transesterification method is a simplified method for biodiesel production where the oil was simultaneously extracted and transesterified into alkyl ester in-situ in one single process. This process combines the steps of lipid (oil) extraction and transesterification. The alcohol used was methanol as it is widely available and economically feasible. In this study, in situ transesterification was conducted using solid coconut waste and a novel heterogeneous catalyst synthesized from eggshells and solid coconut waste by calcination. Reaction temperature, catalyst loading, and methanol to solid ratio were varied from 70 to 120˚C, 0.5 to 10.5 wt %, and 8:1 to 12:1 respectively. Meanwhile, reaction time was fixed to 3 hrs. Heterogeneous catalyst can help to reduce the steps in separation and purification of the product. Moreover, utilizing waste in the production can lower the production cost as well as help to save and clean the environment. The highest biodiesel yield was observed at the condition of 95˚C, 0.5 wt % catalyst, and 10:1 methanol to solid ratio.